ANALISIS PERMUKAAN ZEOLIT ALAM MALANG YANG MENGALAMI MODIFIKASI PORI DENGAN UJI SEM-EDS - Anton Prasetyo; Rini Nafsiati; Susi Nurul Kholifah; Agie Botianovi (SAINSTIS, 2012)
Nature zeolit is pore material much benefitted in industry sector as adsorben, katalis and many other else. The existence of this material in Indonesia is very exuberate, one of them is Malang. The efforts to improve zeolit quality have already much done by many researchers. In this research, there has been done characterization and zeolit modification in Malang land become mesopori material by using surfaktan CTAB as template. To characterize pore can be done by SEM test and to know the element content can be done by EDS test. From this, we know that from SEM test got result that mophologi structure of zeolit grain generally contains lempengs arranged insmoothly and tend to be amorf shape. SEM test is incapable to identify pore of zeolit such as   preparasi, kalsinasi or modified zeolit in order unidentified took pore changing. The result of EDS test occur that the changing of element content of nature zeolit composer in dealuminasi process. So there is changing of ratio Si/Al in nature zeolit where it is 3.002   and   after   dealuminasi   1.8994.   Whereas   the   element   content   after modification is similar with element content in zeolit having dealuminasi.